Brief report: Self-compassion, physical health and the mediating role of health-promoting behaviours. (June 2018) - Dunne, Sara; Sheffield, David; Chilcot, Joseph
To test the hypothesis that self-compassion predicts better physical health and that this is partially mediated through health-promoting behaviours, 147 adults completed self-report measures of self-compassion, health-promoting behaviours and physical health. Self-compassion and health-promoting behaviours were negatively associated with physical symptom scores. Self-compassion was positively associated with health-promoting behaviours. A bootstrapped mediation model confirmed a significant direct effect of self-compassion on physical health through health-promoting behaviours ( R 2 = 0.13, b = −8.98, p = 0.015), which was partially mediated through health-promoting behaviours ( R 2 = 0.06, b = −3.16, 95 per cent confidence interval [−6.78, −0.86]). Findings underscore the potential health-promoting benefits of self-compassion.